Microbiological challenge testing of Listeria monocytogenes in virgin coconut oil - Rigor, Theresa Marie T. (College of Home Economics, University of the Philippines Diliman, 2020)
Cold-pressed virgin coconut oil (VCO) is produced without undergoing harsh thermal or chemical processes. As a ready-to-eat food, minimal processing makes VCO high-risk. Microbiological challenge testing of L. monocytogenes artificially inoculated in VCO for long-term storage at 35°C and 45°C was conducted to investigate the effect of temperature storage on the fate of L. monocytogenes in VCO. Enumeration of L. monocytogenes throughout the storage period was fitted (GinaFiT). At 35°C, biphasic inactivation behavior preceded by a shoulder was exhibited (t4D=22.44 days), suggesting that the food matrix's composition and physicochemical properties in thermal storage inhibited the bacteria's growth. The consumer study (n=35) found that 71.34% of the consumers consumed VCO directly with no further heating. Most stored their VCO products in appropriate temperatures, but do not distinguish between VCO products registered as a food product versus those listed as cosmetics under FDA registry, which can be risky due to regulation discrepancies. This study may serve as a baseline for revisions in the current standards for the processing, storage, and marketing of VCO in the Philippines. Research on changes in physicochemical properties due to storage temperature is recommend